Preparation of a magnetic egg yolk shell nitrogen and phosphorus doped carbon nanocage material and its application in the detection of breve dinoflagellates toxins

By using magnetic solid phase extraction of nitrogen-phosphorus doped carbon nanocage materials with magnetic egg yolk shell structure in seawater, the problems of low sensitivity of trace short nude dinoflagellate toxin detection in complex substrates and complex sample pretreatment are solved, achieving high efficiency , reliable enrichment and separation simplifies the operation process and improves the accuracy and stability of detection.

CN116037062BActive Publication Date: 2025-01-17FUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211647002.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-01-17
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

The prior art has problems of low sensitivity, complex and time-consuming when detecting trace short nude dinoflagellin in complex substrates, especially when the algatoxin contamination range is expanded and the content is reduced, effective pre-preparation is required. Processing methods to improve the reliability of analysis results.

Method used

Using a magnetic egg yolk shell structure based on MOF-derived nitrogen-phosphorus doped carbon nanocage material as adsorbent, it was synthesized by calcination and combined with magnetic solid phase extraction (MSPE) and high performance liquid chromatography-mass spectrometry (HPLC-MS/MS) , realize fast and easy sample enrichment and separation.

Benefits of technology

Improves the enrichment and extraction efficiency of trace algatoxins in complex substrates, reduces detection limits, expands linear range, simplifies the operation process, and the high stability and porous structure of the material enable it to be reused multiple times, and recovered Up to 86%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116037062B_ABST
    Figure CN116037062B_ABST
Patent Text Reader

Abstract

The present invention discloses the preparation of a magnetic yolk-shell nitrogen-phosphorus-doped carbon nanocage material and its use for the detection of breve toxin. The doping of nitrogen and phosphorus elements can improve the surface defects of the material, increase the adsorption sites, and improve the adsorption performance. At the same time, the material with yolk-shell structure has a better enrichment effect than the block morphology, which may be attributed to the larger surface area and shorter diffusion path. The present invention uses ZIF-67 as a self-sacrificial template to greenly and controllably synthesize Y-N, P-CNCs with yolk-shell structure. The prepared Y-N, P-CNCs material has the advantages of unique hierarchical porous structure, high stability, strong magnetic response, high hydrophilicity, etc. The material is used as an adsorbent for magnetic solid-phase extraction and combined with HPLC-MS / MS to establish a detection method for breve toxin. The established method has a good adsorption effect, indicating that the material has good application prospects in the field of sample pretreatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a MOF-derived magnetic yolk shell nitrogen and phosphorus-doped carbon nanocage material and the use of the material in detecting breve dinoflagellates toxins in seawater. Background Art

[0002] Cyanobacteria are widely distributed photoautotrophic microorganisms that release a chemical substance called algal toxins during reproduction or when they are about to die, posing a threat to aquatic organisms and mammals. Algal toxins are the pollutants that appear most frequently and cause the most serious harm in harmful cyanobacterial blooms. The main methods for detecting algal toxins in water bodies are high performance liquid chromatography and liquid chromatography-mass spectrometry. High performance liquid chromatography has low sensitivity and requires enrichment of large volumes of water samples for determination. Liquid chromatography-mass spectrometry has high sensitivity and is currently the most commonly used method for detecting algal toxins. However, with the continuous expansion of the scope of algal toxin pollution, the actual sample types that need to be analyzed are becoming more and more complex, and the content is becoming lower and lower. Therefore, before the instrument sampling and analysis, a certain degree of sample pretreatment is required to reduce the interference of the sample matrix, improve the sensitivity of the analysis method, and reduce instrument contamination, thereby ensuring the reliability of the analysis results.

[0003] Solid phase extraction is a pretreatment technology that uses adsorbent materials to selectively enrich, separate and purify the sample to be tested through adsorption, washing, elution and other processes. Proposed by Waters Co in 1978, its working principle is the interaction between the adsorbent and the analyte. Its advantages such as high efficiency, reliability and low reagent consumption have made it widely used in environmental analysis. However, SPE extraction columns have the disadvantages of easy clogging, complex operation process and long time consumption. Therefore, in view of this defect, the strategy of selecting magnetic functional particles as adsorbents can greatly simplify the sample pretreatment process by eliminating operations such as centrifugation and filtration.

[0004] Carbon-based nanomaterials have shown great potential in analytical detection applications due to their unique chemical and physical properties (including high stability and good mechanical strength). However, the hydrophobicity and lack of active sites of carbon materials limit their adsorption applications. The present invention aims to establish a pretreatment detection method for trace breve toxins in complex matrices. Using ZIF-67 as a self-sacrificial template and natural and environmentally friendly phytic acid as a protective etchant and phosphorus source, a nitrogen-phosphorus doped carbon nanocage material with a yolk shell structure is designed in a green and controllable manner. The material obtained by the present invention has a unique hierarchical porous structure, high stability, strong magnetism, and good adsorption performance. The doping of nitrogen and phosphorus elements not only enables the material to have a large number of adsorption sites, but also improves the surface hydrophobicity of the carbon material, which is conducive to improving the enrichment and extraction of trace algae toxins in complex matrices. Therefore, it is reliable and effective to use the material in the pretreatment process of breve toxins in complex actual samples. Summary of the invention

[0005] The present invention simply synthesizes a magnetic yolk-shell-structured nitrogen and phosphorus codoped carbon nanocage adsorbent material (yolk-shell-structured nitrogen and phosphorus codoped carbon nanocages, YN, P-CNCs) by a calcination method. The yolk-shell-structured magnetic nitrogen and phosphorus codoped carbon nanocages as an adsorption material not only have a high specific surface area, but also have a large number of adsorption sites due to the doping of nitrogen and phosphorus elements, and improve their dispersibility in water. The yolk-shell structure enables it to have a unique hierarchical porous structure, which greatly reduces the mass transfer distance between the target and the adsorbent. At the same time, its strong magnetic response is conducive to the adsorbent material to achieve fast and simple solid-liquid separation during the adsorption and analysis process. Combined with MSPE-HPLC-MS / MS, the prepared magnetic yolk-shell-structured nitrogen and phosphorus codoped carbon nanocage material is applied to the adsorption and enrichment of breve dinoflagellates toxin in seawater, and breve dinoflagellates toxin is effectively adsorbed under optimal conditions, and the established detection method has a low detection limit and a wide linear range.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] 1 A method for synthesizing YN,P-CNCs material, comprising the following steps:

[0008] 1.1 Preparation of ZIF-67

[0009] 1.1.1 Weigh 3.2 g of 2-methylimidazole and dissolve it in 70 mL of methanol. Dissolve it thoroughly by ultrasonication. Then, dissolve 1.4 g of Co(NO3)2·6H2O in 30 mL of methanol. Dissolve it thoroughly by ultrasonication. Then, mix the two clear solutions, stir them thoroughly, and let them stand at room temperature for 12 h.

[0010] 1.1.2 After the reaction was completed, the product was centrifuged and washed with methanol until it was colorless. The centrifugal washing speed was 8000 rpm and the time was 5 min. The product was dried at 60 °C for 12 h to obtain ZIF-67.

[0011] 1.2. Preparation of Y-ZIF67@CoPA

[0012] 1.2.1 Weigh 0.3 g-0.5 g of the ZIF-67 powder prepared above and 0.3 g-0.5 g of polyvinyl pyrrolidone, dissolve in 300 mL-500 mL of methanol, add 400 mL of 0.5-2.0 mM phytic acid solution while stirring, and react at room temperature with stirring for 1 h.

[0013] 1.2.2 After the reaction is completed, transfer the solution to a centrifuge tube and wash it with methanol by centrifugation until it becomes neutral. The centrifugal washing speed is 5000 rpm and the time is 5 min.

[0014] 1.2.3 After centrifugal washing, the product was dried at 60 °C for 12 h to obtain Y-ZIF67@CoPA material.

[0015] 1.3 Preparation of yolk shell magnetic nitrogen and phosphorus doped carbon nanocages (YN,P-CNCs)

[0016] 1.3.1 Weigh 2.0 g of the Y-ZIF67@CoPA powder obtained above and fully calcine it in a tubular furnace with a mixed gas of Ar / H2 (95% / 5%, v / v). The temperature is set to rise from 25 ℃ to 450-700 ℃ (preferably 550 ℃) at a rate of 5 ℃ / min and keep warm for 2 h. After the reaction is completed, cool to room temperature at a rate of 10 ℃ / min to obtain egg yolk shell-shaped cobalt-containing nitrogen and phosphorus doped carbon nanocages (YN,P-CNCs). Grind the obtained product for later use.

[0017] 2 The obtained YN,P-CNCs material was used as a magnetic solid phase extraction (MSPE) adsorbent material, combined with HPLC-MS / MS, to detect the content of breve toxins in seawater. The specific steps are as follows:

[0018] 2.1 Add 20 mL of standard aqueous solution (250 pg / mL) or sample solution into a 50 mL centrifuge tube. Then, take 0.5 mg of magnetic YN,P-CNCs powder and disperse it into 20 mL of the prepared solution.

[0019] 2.2 To promote the adsorption of breve toxins onto the adsorbent, the mixture was adsorbed for 10 min using shaking. Next, the adsorbent was collected by separation with the help of an external magnetic field, and the supernatant was discarded.

[0020] 2.3 Desorb the analytes from the adsorbent with 3 mL of ethyl acetate / acetonitrile (80% / 20%, v / v) under vortexing for 15 min, and collect the eluate by magnetic separation. The collected eluate was dried with nitrogen at room temperature and reconstituted with 0.5 mL of methanol for HPLC-MS / MS analysis.

[0021] The advantages of the present invention are:

[0022] 1) The method of the present invention is simple to operate, green and friendly, low in cost and has stable reaction products. The prepared YN,P-CNCs have a large specific surface area (72.93 m 2 / g) and good adsorption capacity (adsorption capacity Qmax At 412.5 ug g -1 About 3000 ℃), which can effectively enrich trace amounts of algae toxins in water.

[0023] 2) The material obtained by the present invention improves the hydrophobicity of conventional carbon materials by doping with nitrogen and phosphorus elements, increases the adsorption active sites of the material, and thus improves its adsorption performance in water. At the same time, the prepared material has excellent chemical stability and mechanical stability, and can be reused many times (after each use, the adsorbent material is washed three times in methanol and then dried under vacuum. After 10 extraction and reuse cycles, the recovery rate is as high as 86%). The yolk shell structure has a unique layered porous structure, which greatly reduces the mass transfer distance between the target and the adsorbent.

[0024] 3) The magnetic nitrogen-phosphorus doped carbon nanocage prepared by the present invention is a yolk-shell structure (the outer shell is a cobalt-phosphorus compound, and the inner yolk is a composite of metal cobalt and nitrogen-doped carbon nanomaterials), which can provide a large specific surface area, and its hierarchical pore nanostructure design is conducive to exposing more active sites and shortening the mass transfer distance of the target. In addition, the doping of nitrogen and phosphorus heteroatoms can improve the hydrophobicity of carbon materials and provide more active sites, thereby improving adsorption performance. The carbonized main structure has good chemical stability and forms strong π-π and hydrophobic interactions with the benzene ring of the target, which has good application prospects in the separation and detection of complex matrices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Transmission electron microscope images of YN, P-CNCs materials;

[0026] Figure 2 The pH optimization diagram of YN,P-CNCs materials for the magnetic solid phase extraction of breve dinoflagellates toxins;

[0027] Figure 3 This is the optimization diagram of adsorbent dosage for YN,P-CNCs materials used in magnetic solid phase extraction of breve dinoflagellates toxins;

[0028] Figure 4 This is the optimization diagram of the adsorption time of short naked dinoflagellates toxins using YN, P-CNCs materials in magnetic solid phase extraction;

[0029] Figure 5 The optimized analysis solution diagram of YN, P-CNCs materials for magnetic solid phase extraction of breve dinoflagellates toxins;

[0030] Figure 6 This is the optimization diagram of the elution time of short naked dinoflagellates toxins using YN, P-CNCs materials in magnetic solid phase extraction;

[0031] Figure 7The chromatograms of the YN,P-CNCs material obtained in the present invention after extraction of breve toxin (a) and the chromatograms of breve toxin standards added with 10 pg / mL (b), 50 pg / mL (c), and 250 pg / mL (d);

[0032] Figure 8 The recycling performance of YN,P-CNCs materials for breve toxin;

[0033] Fig. 9 These are the adsorption isotherms of YN, P-CNCs materials and CNCs materials. DETAILED DESCRIPTION

[0034] The present invention will be further described in detail below in conjunction with the embodiments of the accompanying drawings. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.

[0035] Embodiment 1:

[0036] A method for synthesizing a magnetic yolk-shell structure nitrogen-phosphorus-doped carbon nanocage material, comprising the following steps:

[0037] 1) Preparation of ZIF-67

[0038] a) Weigh 3.2 g of 2-methylimidazole and dissolve it in 70 mL of methanol. Ultrasonicate for 1 min to fully dissolve it. Then, take another 1.4 g of Co(NO3)2·6H2O and dissolve it in 30 mL of methanol. Ultrasonicate for 1 min to fully dissolve it. Mix the two clear solutions, stir them thoroughly, and let them stand at room temperature for 12 h.

[0039] b) After the reaction is completed, the obtained product is centrifuged and washed with methanol until it becomes colorless, the centrifugal washing speed is 8000 rpm, and the time is 5 min. The obtained product is dried at 60 ° C for 12 h to obtain ZIF-67.

[0040] 2) Preparation of Y-ZIF67@CoPA

[0041] a) Weigh 0.3 g of the ZIF-67 powder prepared above and 0.3 g of polyvinyl pyrrolidone, dissolve in 300 mL of methanol, add 400 mL of 1.5 mM phytic acid solution while stirring, and react at room temperature with stirring for 1 h.

[0042] b) After the reaction is completed, the solution is transferred to a centrifuge tube and washed by centrifugation with methanol until neutral. The centrifugal washing speed is 5000 rpm and the time is 5 min.

[0043] c) After centrifugal washing, the product was dried at 60 °C for 12 h to obtain Y-ZIF67@CoPA material.

[0044] 3) Yolk shell magnetic nitrogen and phosphorus doped carbon nanocages (YN,P-CNCs)

[0045] a) Weigh 2.0 g of the Y-ZIF67@CoPA powder obtained above and fully calcine it in a tubular furnace with a mixed gas of Ar / H2 (95% / 5%, v / v). The temperature was set to rise from 25°C to 550°C at a rate of 5°C / min and then maintained at 550°C for 2h. After the reaction was completed, the temperature was lowered to room temperature at a rate of 10°C / min to obtain egg yolk-shell-shaped cobalt-containing nitrogen-phosphorus-doped carbon nanocages (YN,P-CNCs). The obtained product was ground for later use.

[0046] Figure 1 This is the TEM (transmission electron microscope) image of YN,P-CNCs. It can be clearly seen from the image that the morphological structure of the material is a carbon nanocage with a yolk-shell structure.

[0047] Application Examples

[0048] The material synthesized in Example 1 was used as a magnetic solid phase extraction material and combined with HPLC-MS / MS to extract breve dinoflagellates from seawater. Under the set chromatographic method, the amount of adsorbent, pH, extraction time, analytical solution, and desorption time were optimized. In order to obtain the best extraction effect, 250 pg mL -1 In the BTX standard solution, a series of important factors affecting the performance of MSPE, such as solution pH, adsorbent dosage, adsorption time, desorption solution and desorption time, were optimized. The results are shown in Figure 2-Figure 6 The optimal conditions were: pH = 7; adsorbent dosage: 0.5 mg; adsorption time: 5 min; desorption solution: ethyl acetate / acetonitrile (80% / 20%, v / v); desorption time: 15 min. Subsequently, the method was established and verified under the optimal conditions.

[0049] Under the optimal conditions, the algal toxins in seawater are detected. The specific steps are as follows:

[0050] 1. Add 20 mL of standard aqueous solution (250 pg / mL) or sample solution into a 50 mL centrifuge tube. Then, take 0.5 mg of magnetic YN,P-CNCs powder and disperse it into 20 mL of the prepared solution.

[0051] 2. To promote the adsorption of breve toxins onto the adsorbent, the mixture was adsorbed for 10 min using shaking. Next, the adsorbent was collected by separation with the help of an external magnetic field, and the supernatant was discarded.

[0052] 3. Desorb the analytes from the adsorbent with 3 mL of ethyl acetate / acetonitrile (80% / 20%, v / v) under vortexing for 15 min, and collect the eluate by magnetic separation. The collected eluate was dried with nitrogen at room temperature and reconstituted with 0.5 mL of methanol for HPLC-MS / MS analysis.

[0053] 4. Chromatographic conditions: Mobile phases A (0.1% formic acid and 50 mM ammonium formate in water) and B (pure methanol); isocratic elution on a Hypersil GOLD column (5 μm particle size, 150×2.1 mm) with 5% A and 95% B at a flow rate of 200 μL min -1 .

[0054] 5. Under the optimal conditions, examine the linear range, detection line, sensitivity, etc. of the method.

[0055] The obtained method has a wide linear range (5.0-1000.0 pg·mL -1) , good linearity (R = 0.9993) and low detection limit (2.0 pg·mL -1 To verify the accuracy of the established method in practical applications, the concentrations of 10, 50 and 250 pg mL -1 Spiking tests were carried out at three concentration levels and the recoveries of this method were 83.5 - 105.4%.

[0056] Figure 7 :The material was extracted and verified by spiked experiments. The spiked recovery of this method was 83.5-105.4%, indicating that the method has good accuracy and reproducibility. The typical chromatogram of the seawater spiked sample is shown in Figure 7 shown.

[0057] Figure 8 :The prepared YN,P-CNCs materials were tested for the number of times they were recycled. Under the optimal MSPE conditions, the recovery rate was as high as 86% after 10 cycles. The results show that magnetic YN,P-CNCs are very stable and recyclable.

[0058] like Fig. 9 As shown in Figure 2, the maximum adsorption capacity of BTX-1 for YN, P-CNCs and CNC materials is 412.5 and 228.8 ug g, respectively. -1, indicating that doping with nitrogen and phosphorus elements can improve surface defects of materials, increase adsorption sites, and improve adsorption performance.

[0059] Nitrogen and phosphorus doping improves the hydrophilicity of the material, which is conducive to the dispersion of the material in the water medium and better contact with the target. At the same time, the yolk shell structure has a unique layered porous structure, which greatly reduces the mass transfer distance between the target and the adsorbent. These characteristics make the developed YN, P-CNCs material reach adsorption equilibrium within 10 minutes in the adsorption kinetics curve of BTX-1, while the traditional CNCs material takes 20 minutes to reach adsorption equilibrium, proving that the YN, P-CNCs material can achieve rapid adsorption.

[0060] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. Application of a magnetic egg yolk shell nitrogen and phosphorus doped carbon nanocage material in the detection of breve dinoflagellates toxin, characterized in that: The preparation method of the magnetic egg yolk shell nitrogen and phosphorus doped carbon nano cage material comprises the following steps: 1) Preparation of ZIF-67 a) Weigh 3.2 g of 2-methylimidazole and dissolve it in 70 mL of methanol by ultrasonic dissolution; then take another 1.4 g of Co(NO3)2·6H2O and dissolve it in 30 mL of methanol by ultrasonic dissolution. After the two solutions are mixed, stir them thoroughly and let stand at room temperature for 12 h; b) After the reaction is completed, the obtained product is centrifuged and washed with methanol until it is colorless, the centrifugal washing speed is 8000 rpm, and the time is 5 min; the obtained product is dried at 60 ° C for 12 h to obtain ZIF-67; 2) Preparation of Y-ZIF67@CoPA materials a) Weigh 0.3 g-0.5 g of ZIF-67 powder and 0.3 g-0.5 g of polyvinyl pyrrolidone, add 300 mL-500 mL of methanol, add 400 mL of phytic acid solution while stirring, and react at room temperature with stirring for 1 h; b) After the reaction is completed, the solution is transferred to a centrifuge tube and centrifuged with methanol until neutral. The centrifugal washing speed is 5000 rpm and the time is 5 min; c) After centrifugal washing, the product was dried at 60 °C for 12 h to obtain Y-ZIF67@CoPA material; 3) Preparation of magnetic yolk shell nitrogen and phosphorus doped carbon nanocage materials 2.0 g of Y-ZIF67@CoPA powder was weighed and fully calcined in a tubular furnace filled with a mixed gas of Ar / H2 with a volume percentage concentration of 95% / 5%. The temperature was set to first rise from 25 °C to 450-700 °C at a rate of 5 °C / min and keep at this temperature for 2 h. After the reaction was completed, the temperature was cooled to room temperature at a rate of 10 °C / min to obtain a cobalt-containing magnetic yolk shell nitrogen-phosphorus-doped carbon nanocage material.

2. The use according to claim 1, characterized in that: The calcination temperature in step 3) is 550°C.

3. The use according to claim 1, characterized in that: The concentration of the phytic acid solution in step 2) is 0.5 mM-2.0 mM.

Citation Information

Patent Citations

  • Method for preparing MOF (metal organic frameworks)-based magnetic nitrogen-doped carbon nano-tubes and application thereof

    CN108525635A